If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10+-3x=-5+2x
We move all terms to the left:
10+-3x-(-5+2x)=0
We add all the numbers together, and all the variables
-3x-(2x-5)+10+=0
We add all the numbers together, and all the variables
-3x-(2x-5)=0
We get rid of parentheses
-3x-2x+5=0
We add all the numbers together, and all the variables
-5x+5=0
We move all terms containing x to the left, all other terms to the right
-5x=-5
x=-5/-5
x=1
| n^2-3n+23=0 | | 13x+4=13x-5 | | 0.63=0.5^x | | -448=46q | | a−3=34 | | x/2-5=x/2-7 | | 2x-40=125 | | 3^{x-2}-61=6500 | | 2y-20=y+30 | | {8m-5m=-11 | | 0=7n-n2+60 | | 8m-5m=-11 | | m2-m=12 | | m2=m=12 | | 5z-9=46 | | p2+18p=-65 | | 4b=72-b2 | | 3x+4(x+2)=7x+11 | | 7x2+24x=-20 | | 5v2-2v=16 | | 2x-3=6x=13 | | 0=70-k2+3k | | x2=-4+4x | | -m=12-m2 | | -24=-m2+5m | | 45-23=2x | | g-8=23 | | u+14=19 | | q÷9=7 | | x⁵+x²=0 | | n÷8=5 | | -1/(x+2.5)-25=0 |